212k views
23 votes
9+4f-7z use f=6 and z=5

User CFinck
by
4.2k points

2 Answers

8 votes

Answer: -2

9 + 4f - 7z

Use what they have given you

f = 6

z = 5

Now that you have those, all you need to do is substitute them into the expression

9 + 4f - 7z

9 + 4 (6) - 7 (5)

9 + 24 - 35

33 - 35

-2

User Gary Liu
by
4.9k points
4 votes

Answer:

-2

Explanation:

9 + 4f - 7z

Use what they have given you

f = 6

z = 5

Now that you have those, all you need to do is substitute them into the expression

9 + 4f - 7z

9 + 4 (6) - 7 (5)

9 + 24 - 35

33 - 35

-2

Hope this helped!

Have a supercalifragilisticexpialidocious day!

User Shishir Kumar
by
4.6k points